PELATIHAN PEMBUATAN BAHAN AJAR BERBASIS MULTIMEDIA BAGI GURU-GURU AL YASINI PASURUAN - Khudzaifah, Muhammad; Sa'adati, Hawzah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Multimedia provides opportunities for educators to develop learning techniques so as to produce maximum results, with multi media it is hoped that they will be easier to determine with what and how students can absorb information quickly and efficiently. Until now, interactive learning media has not been developed optimally in Indonesia. One obstacle in the development of interactive learning media is the lack of mastery of interactive media development technology by teachers, so the development of interactive learning materials with computers is less than optimal. This online-based learning media development training that will be developed and applied for teachers at the Al Yasini Pasuruan Foundation is expected to provide new insights in making instructional media, given the ability of this program in terms of making animations for attractive online-based learning media in a relatively easy way . With the mastery of online-based learning media by the teachers at the Al Yasini Pasuruan Foundation, it is hoped that it will trigger students' interest to be more enthusiastic in following the lessons, and ultimately will improve the overall quality of learning.